Reforming Taxation System under Conditions of European Integration - Zhuk, Olha (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article discusses the importance of tax reform and the issues associated with it. The author develops a stage-by-stage approach to reforming Ukraine’s taxation system considering modern tendencies and the country’s move towards integration in Europe. The paper also analyzes the characteristics of Ukraine’s taxation system, argues for the necessity to change it and identifies taxation policy development priorities under conditions of European integration